Histoire de la France urbaine (Seuil)
Bibl. 2: La ville médiévale : des Carolingiens à la Renaissance / par André Chédeville. Jacques Le Goff, Jacques Rossiaud, dir. par Jacques Le Goff. - 1980. - 653 p. - ISBN 2-02-005666-6